Stance expressions in applied linguistics research articles: A corpus-based contrastive study - Muchamad Sholakhuddin Al Fajri; Ikmi Nur Oktavianti (Peoples' Friendship University of Russia (RUDN University), 2024)
Stance, a crucial aspect of academic writing, is complex and vital for both beginner and advanced writers. However, L2 English learners and experienced writers frequently struggle with using stance markers effectively. Currently, there remains a scarcity of research comparing the utilisation of stance markers in applied linguistics research articles between native English professional writers and L1 Indonesian speakers. This study aims to fill this gap by investigating similarities and differences in the deployment of stance markers in applied linguistics research articles by authors with L1 Indonesian and L1 English backgrounds and discussing the educational implications derived from the analysis results. The analysis involves two corpora: the Indonesian academic corpus (IAC), comprising articles authored by L1 Indonesians, and the English academic corpus (EAC), consisting of articles by native English speakers. The study investigates various types of stance markers and their distribution across the corpora, revealing significant differences in their usage. L2 English authors employ more boosters and attitude markers, while L1 English writers use more hedges and self-mentions, with the most notable disparities observed in the usage of self-references. These findings underscore the necessity for educators, particularly within the Indonesian context, to sensitise learners to the discursive norms surrounding the use of stance markers in applied linguistics research articles and provide targeted instruction to enhance English learners' proficiency in employing stance markers effectively.